Research progress on the regulation of production traits by gastrointestinal microbiota in dairy cows - Liu, Lily; Wu, Peifu; Guo, Aiwei; Yang, Yajin; Chen, Fenfen; Zhang, Qin (Frontiers in Veterinary Science, 2023)
The composition and abundance of microorganisms in the gastrointestinal tract of cows are complex and extensive, and they play a crucial role in regulating nutrient digestion, absorption, maintaining digestive tract stability, and promoting the production and health of the host. The fermentation carried out by these microorganisms in the gastrointestinal tract is fundamental to the health and productivity of cows. Rumen microorganisms produce the majority of enzymes required to break down feed substrates, such as cellulose, protein, lipids, and other plant materials, through fermentation. This process provides energy metabolism substrates that satisfy approximately 70% of the host's energy requirements for physiological activities. Gut microorganisms primarily decompose cellulose that is difficult to digest in the rumen, thereby providing heat and energy to the hosts. Additionally, they have an impact on host health and productivity through their role in immune function. Understanding the composition and function of the cow gut microbiota can help regulate dairy cattle breeding traits and improve their health status. As a result, it has become a popular research topic in dairy cattle breeding. This article provides a review of the composition, structure, physiological characteristics, and physiological effects of the cow gut microbiota, serving as a theoretical foundation for future studies that aim to utilize the gut microbiota for dairy cattle breeding or improving production traits. It may also serve as a reference for research on gut microbiota of other ruminants.